The Importance of a Chief Sustainability Officer (CSO) in Multinational and State-Owned Enterprises - Ardi Ardi; Hadi Cahyadi; Rudi Sarwono; Handoko Limaho; Yohana F. C. P. Meilani; Rudy Pramono (Journal of Human, Earth, and Future, 2023)
This study examines the function of chief sustainability officers (CSOs) in state-owned enterprises (SOEs) and multinational enterprises (MNEs) doing business in Indonesia, with a focus on their initiatives to achieve net-zero carbon dioxide (CO2) emissions by 2050. This project highlights the value of having a Chief Sustainability Officer (CSO) in Indonesian MNEs and SOEs. These organizations must acknowledge that they currently lack a CSO at the director level and must assign a CSO to their organizational structure. Strategic leadership, regulatory compliance, stakeholder engagement, innovation and technology adoption, risk mitigation, cost savings, carbon accounting and reporting, and competitive advantage are critical strategic CSOs for Indonesian MNEs and SOEs beyond guaranteeing sustainability. Seventy-six sustainability reports from State-Owned Enterprises (SOEs) and Multinational Enterprises (MNEs) operating in Indonesia listed on the Indonesia Stock Exchange for 2021–2022 are the documents studied in the approaches. The results indicate that a critical prerequisite for long-term development and a way to meet sustainability goals is for Indonesian MNEs and SOEs to designate a CSO. The CSO is essential in promoting sustainable practices, reducing risks, ensuring compliance, and enhancing the company's image in a society that is becoming more environmentally conscious. Establishing and strengthening the CSO role should be a top priority for these organizations if they want to reach their goal of being net-zero emitters of CO2by 2050.